Systematic reviews on the effectiveness of the ABC HIV prevention strategy in South Africa / Nkgethi Patricia Mmushi - Mmushi, Nkgethi Patricia (2016)
The objectives of the study are to explore the effectiveness of the ABC HIV prevention strategy in South Africa with the purpose of establishing problem areas of the ABC HIV prevention strategy in South Africa. A systematic review design was followed. Electronic databases; Google scholar, Medline and PubMed were searched using broad combination of keywords to obtain all relevant articles. Studies written in English, published between 2000 and 2010, were selected if they met the inclusion criteria. In order to be included the study had to discuss the ABC HIV prevention strategy with the focus on effectiveness of the strategy. The Critical appraisal instrument for qualitative research studies (CASP, 2006) and Quality Assessment Tool for Quantitative studies (Effective Public Health Practice Project, 2005) were used to critically appraise the 9 studies that met the inclusion criteria. Thematic analysis was used for the analysis process. The findings regarding each objective were combined in a summary of findings. The findings revealed that the South African population engages in sexual activities at an early age. Males and females have concurrent sexual partnerships, which mean they are not faithful to their primary sexual partners and lastly, women are unable to use or negotiate condom use. Identified problem areas of the ABC HIV prevention strategy in South Africa were that the age gap between sexual partners is a problem as women cannot negotiate condom use with their seniors. The notion of love and romance that influences the use of condoms, has a negative impact whereby condom use is unacceptable in a long term relationship, irrespective of the level of faithfulness. Low socio-economic status of women that makes women to be dependent on men and also prone to engage in transactional sex. Lastly, local norms about sexuality that men subscribe to, to prove masculinity. === Thesis (M.Cur) North-West University, Mafikeng Campus, 2011